Closure of open window thoracostomy due to MRSA pyothorax by EWS bronchial occlusion and modified extraperiosteal air plombage: a case report - Masami Kuramochi; Mayumi Shinonaga; Setsuo Kuraoka (Surgical Case Reports, 2024)
Abstract Background Refractory pyothorax caused by methicillin-resistant Staphylococcus aureus (MRSA) is a challenging clinical condition; complications such as bronchopleural fistulae can further hinder its treatment. To avoid a fatal state caused by aspirating pneumonia, open window thoracotomy is not only sometimes performed, but subsequent closure of the window can also be difficult. In this report, we describe the case of a patient with MRSA pyothorax with bronchopleural fistula in whom a successful closure of window thoracostomy was achieved by utilizing Endobronchial Watanabe Spigot　(EWS; Novatech, La Ciotat, France) bronchial occlusion and a modified extraperiosteal air plombage technique. Case presentation A 66-year-old man underwent an open window thoracotomy for pyothorax with bronchopleural fistula with MRSA infection at the age of 59. After 7 years, he was referred to our department for the closure of the window. Initially, we occluded the right B6a + b by EWS under bronchoscopy. Subsequently, we dissected the intercostal muscles between the 3rd, 4th, 5th, and 6th ribs to collapse the pyothorax cavity and ensure the coverage of the fistula of lung including the hypertrophied parietal pleura and soft tissues of the chest wall. We filled the extrapleosteal space with a pedicled anterior serratus muscle flap to compress the parietal pleura. Postoperatively, lung expansion was satisfactory, and there has been no recurrence for 6 years since the window closure surgery. Conclusions We were able to achieve closure and healing in a patient who underwent open window thoracostomy for MRSA bronchopleural fistula by applying EWS and modified extraperiosteal air plombage technique.